2001
DOI: 10.1053/rapm.2001.22997
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal fentanyl-induced pruritus is more severe in combination with procaine than with lidocaine or bupivacaine

Abstract: Procaine produces a higher frequency of pruritus than that seen with lidocaine-fentanyl combinations and a greater severity of pruritus than seen with lidocaine-fentanyl and bupivacaine-fentanyl spinal anesthesia. Reg Anesth Pain Med 2001;26:252-256.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
(21 reference statements)
2
5
0
Order By: Relevance
“…Among all the side effects of intrathecal opioids, pruritus (50 -75%) was most common. This corroborates with a recent study 46 which reported a higher incidence of pruritus with knee arthroscopy than other surgical patients, and pruritus further increased with the use of bupivacaine rather than lignocaine. The increased pruritus can be a disadvantage in day care patients in whom anaesthetic management is tailored to reduce side effects.…”
Section: Discussionsupporting
confidence: 92%
“…Among all the side effects of intrathecal opioids, pruritus (50 -75%) was most common. This corroborates with a recent study 46 which reported a higher incidence of pruritus with knee arthroscopy than other surgical patients, and pruritus further increased with the use of bupivacaine rather than lignocaine. The increased pruritus can be a disadvantage in day care patients in whom anaesthetic management is tailored to reduce side effects.…”
Section: Discussionsupporting
confidence: 92%
“…The commonest side‐effect seen in our study was pruritus, which occurred with a frequency of 50–60%; similar to the results of others (13,21). The other major cause for concern is urinary retention after bupivacaine and fentanyl intrathecally.…”
Section: Discussionsupporting
confidence: 92%
“…[ 5 ] Intrathecal fentanyl administration is also associated with high incidence of pruritus in parturients. [ 6 7 8 ]…”
Section: Introductionmentioning
confidence: 99%